Analysis of Some Specific Elements and Speciated Compounds Commonly Found in Fishes in the New Calabar River of the Niger Delta Area, Nigeria - Ndubuisi Kingsley, Owhonda (Contemporary Research and Perspectives in Biological Science Vol. 8, 2025)
Elements like mercury, arsenic, lead and cadmium are well-known to have major human health problems. Elements exist in various forms. While some of these forms are toxic, others are not. The primary purpose of this work was to shed light on the concentrations of these toxic elements since people depend on this river for their source of fish and to also determine their speciated forms in these three fish species. The flesh of Guinean and blackchin tilapia, and mullet found in the New Calabar River (also called Choba River) were collected for elemental studies of mercury, cadmium, lead, arsenic, nickel and speciated forms. The analytical method of X-ray fluorescence (XRF) was used for the elemental studies while a Gas chromatography-mass spectrometer (GC-MS) was used for the speciated forms. The result revealed that 4.3 mg/kg was the highest concentration of cadmium observed in black chin tilapia. The three fish species all contained about 0.5 mg/kg of arsenic and 1 mg/ kg of mercury. 1.7 mg/kg of lead was detected in mullet while 7.3 mg/kg of nickel was detected in blackchin tilapia. Organometallic compounds found were nickel tetracarbonyl, borane carbonyl in Guinean tilapia, nickel tetracarbonyl, borane carbonyl and germanium(iv) pthalocyanine dichloride in blackchin tilapia and [\(\mu\)-(\(\eta\)6-benzene)] bis (\(\eta\)5-2,4-cyclopentadien-yl) di-\(\mu\)-hydrodi-vanadium. Borane carbonyl was found in the mullet. The results showed that toxic elements are present and that the quantity of fish in this river that is consumed is important.